Influence of perceived stress on prenatal depression in Surinamese women enrolled in the CCREOH study - Anisma R. Gokoel; Firoz Abdoel Wahid; Wilco C. W. R. Zijlmans; Arti Shankar; Ashna D. Hindori-Mohangoo; Hannah H. Covert; Meerte-Sigrid Mac; Maureen Y. Lichtveld; Emily W. Harville (BMC, 2021)
Plain language summary Depression during pregnancy may lead to adverse health effects in mothers and children. While one in five pregnancies resulted in an adverse birth outcome in Suriname, and perceived stress and depression are important risk factors for birth outcomes, data on depression and its risk factors are lacking. This study aimed to determine the association between perceived stress and prenatal depression in Surinamese pregnant women participating in the Caribbean Consortium for Research in Environmental and Occupational Health-MeKiTamara study. A total of 1143 pregnant women were included in the study. Using questionnaires, data was collected on demographic factors, perceived stress, social support (including resilience), and probable depression. Perceived stress was somewhat higher during the first two trimesters (27.2%), than the third trimester (24.7%). This was also the case for probable depression; higher during the first two trimesters (22.4%) than during the third trimester (17.6%). The study found a statistically significant association of high perceived stress, low perceived individual resilience, lower education and older maternal age with probable depression during pregnancy. Early detection and effective management of perceived stress and depression during pregnancy are very important. There is a need for prenatal clinics in Suriname to routinely screen for symptoms of perceived stress and depression to minimize the potential impact on mother and child. Health education programs, targeting the reduction of stress during pregnancy, may help to reduce depression and its potential adverse health effects on the mother and child.